Mitologi Tradisi Menunggu Makam Di Desa Bakalan Bojonegoro - Listiani, Intan Dwi; Mevia, Nia Ayu; Salma, Afin Naila; Rosyida, Shela Zaimatur (Program Studi Pendidikan Sejarah - Universitas Samudra, 2024)
This research reveals the mythology and practice of the tradition of waiting for a grave on Friday Legi in Bakulan Village, Bojonegoro. This tradition reflects a blend of spiritual beliefs, local culture, and social values of the Javanese people. This study uses a phenomenological qualitative approach with in-depth observation to explore the meaning of the tradition. This research shows that people believe that if the tradition of waiting for the grave is not carried out, there will be various mystical impacts such as the loss of the pocong rope or the head of the corpse. However, this tradition faces challenges in the modern era including costs, technological changes, time constraints, and the influence of modernization. The tradition of waiting for the grave is still maintained as a form of respecting ancestors and maintaining social harmony in Bakulan Village